Integrative behavioral couple therapy (IBCT) for marital reconciliation: a systematic review of outcomes - Mansor, Abu Talib; Guo, Juncheng; Noradilah, Md Nordin; Anne Noor Sri Juwaneeta, Jamaludin (Sage Publication, 2026)
This systematic review examines the effect of integrative behavioral couple therapy (IBCT) in promoting marital reconciliation among couples experiencing relational distress, with a focus on emotional reattachment as a distinct outcome. Following PRISMA guidelines, five academic databases including PsycINFO, PubMed, Scopus, Web of Science, and EBSCOhost were systematically searched for empirical studies published between 2005 and 2025. Thirteen eligible studies were identified and synthesized to evaluate IBCT's impact on reconciliation-related outcomes, including emotional reattachment, conflict resolution, relational stability, and renewed commitment. Findings indicate that IBCT enhances reconciliation by fostering emotional acceptance, improving communication, and promoting mutual understanding, with key therapeutic mechanisms such as unified detachment, empathic joining, and culturally responsive adaptations. Several studies underscore the importance of communication training, emotional safety, and tailored intervention frameworks. Overall, IBCT appears to be a promising intervention for couples seeking reconciliation, particularly due to its integrated emphasis on behavioral change and emotional acceptance, which supports the complex process of rebuilding trust and relational connection. Future research should further explore cultural adaptation, long-term effectiveness, and integration with complementary therapeutic models.